HUBUNGAN KEPUASAN DAN MOTIVASI MAHASISWA DESAIN KOMUNIKASI VISUAL (DKV) UNIVERSITAS KATOLIK SOEGIJAPRANATA SEMARANG (UNIKA) TERHADAP FITUR PHOTO SHARING DI INSTAGRAM - Aziz, Muhammad Hilmy (Kinesik, 2022)
Instagram became one of the social media with the highest rating of its use among teenagers. There is a wide range of motivations in fulfilling the needs satisfaction. This study aims to determine the relationship of satisfaction and motivation to use Instagram photo sharing feature among students. A total of 148 students who made the study respondents who took the location of research at the Catholic University of Soegijapranata (UNIKA) in the Department of Visual Communication Design (DKV) and has been tested statistically. This research uses descriptive analysis, validity test and reliability test, correlation analysis of Kendal Tau test. From the results of these tests indicate that the existence of positive relations significance between the variable satisfaction and motivation to photo sharing in Instagram.